PENGARUH PAJAK, UKURAN PERUSAHAAN, KEPEMILIKAN ASING, DAN PROFITABILITAS TERHADAP TRANSFER PRICING - Aulia Afridanti Putri; Ameilia Damayanti; Kurnia Heriansyah (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2023)
This study aims to determine the effect of taxes, company size, foreign ownership and profitability on transfer pricing. The independent variables inthis study are taxes, company size, foreign ownership and profitability as measured by return on assets (ROA). The dependent variable in this study istransfer pricing. The population in this study is non-primary tire industry sub-sector companies and automotive retail listed on the Indonesia StockExchange for the 2016-2022 period. The sampling method in this study is purposive sampling so that 35 data were processed. The data analysis method uses multiple regression analysis with the SPSS 26 application. The results of this study show that taxes do not affect transfer pricing, company size does not affect transfer pricing, foreign ownership affects transfer pricing and profitability does not affect transfer pricing. Keywords : Tax, Company Size, Foreign Ownership, Profitability, Tranfer Pricing.